Monitoring training: Where do we go from here? - Foster, C. (Forskningskonferansen 2016, 2016)
1. Monitoring Requires Standard Conditions 2. Nature Boy Training vs Standard Workouts 3. The Lab is Well Suited to Let the Coach Look into the Athletes Eyes at Full Effort 4. Complex Technology=Scientific Discovery, Simple Technology=Coaching 5. Coaches Need to Ask the Questions, Scientists Need to Answer the Questions 6. Sub Elite Athletes are Effective Was to Answer Science Based Questions 7. Lab Testing With Elite Athletes Gives Caches and Scientists a Format to Talk